P30 An evaluation of the use of quality-of-life (qol) scores in pulmonary arterial hypertension. (15th November 2016) - Woolcock, SC; Corris, PA
Abstract : Introduction: Pulmonary Arterial Hypertension (PAH) is a severe, progressive condition leading to increased pulmonary vascular resistance, right ventricular failure and death. PAH is associated with poor prognosis and WHO functional class (FC) is strongly predictive of mortality. Living with PAH has significant physical, psychological and social impact on the lives of patients and carers. Symptoms of depression and anxiety are common and may contribute to poor quality of life (QOL) and social isolation. Although QOL scores have been developed and validated in PAH, the psychological impact of living with PAH is often overlooked. Current guidelines advocate appropriate psychological and social support for patients, however, no formal recommendations exist currently to guide clinicians with regard to the timing and involvement of appropriately skilled professionals. Methods: QOL questionnaire data (Emphasis-10) was collected retrospectively from PAH patients attending routine appointments at PAH nurse and physician-led clinics over a 5 week period (June–July 2016). Results: 56 patients Median age : 62 (31–88) Sex: Male 17 (30%): Female 39 (70%) WHO FC : II: 24 (43%) III: 26 (46%) IV: 6 (11%) Aetiology: Familial: 2 (3%) Portal hypertension: 2 (3%) Connective tissue disease: 8 (14%) Congenital heart disease: 14 (25%) Idiopathic (IPAH): 19 (34%) CTEPH: 12 (21%) Emphasis 10 score (50): FC II: 15 (median), 1–35 (range). FC III: 31 (median), 2 – 50 (range). FC IV: 33 (median), 10–44 (range) Conclusion: Anxiety and depression are common in PAH and can lead to reduced physical and social functioning and poor QOL. The management of physical and psychological symptom burden is important for holistic patient care. Patients with advanced PAH are known to have significantly impaired QOL and this is supported by our data. Whilst QOL scores are recommended in current guidelines and frequently used in clinical practice, there remains uncertainty around the identification and referral of suitable patients to colleagues skilled in psychological interventions and the role for supportive (palliative) care. Our data shows a wide variation in QOL scores within each FC. This shows that psychological support should be considered on an individual patient basis and not only reserved for patients with a poor FC.